THE EFFECT OF DIFFERENT SHADE LEVELS AND DOSAGE OF GOAT MANURE FERTILIZER ON THE GROWTH OF Arachis pintoi ON MEDITERANEAN SOIL - W. A., Bulloh,; Kusumawati, N.N.C.; Witariadi, N. M. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
Forage is a source of nutrition for increasing ruminant livestock production which must be accompanied by the provision of sufficient forage both in quality and quantity.  Plantations or shaded land are an alternative for developing forage. This research aims to determine the interaction and influence of different levels of shade and doses of goat manure on the growth of Arachis pintoi on Mediterranean soil. This research was carried out in Sading Village, Mengwi District, Badung Regency, Bali, lasting 12 weeks from preparation to cutting.  This research used a completely randomized design (CRD) with a factorial pattern. The first factor is the degree of shading: N0= Shading 0%; N1= Shade 20%; N2= Shade 40%; and N3= Shade 60%. The second factor is the dose of goat manure: D1= 10 tons ha-1; D2= 20 tons ha-1; and D3= 30 tons ha-1. There are 12 treatments, namely: N0D1, N0D2, N0D3, N1D1, N1D2, N1D3, N2D1, N2D2, N2D3, N3D1, N3D2 and N3D3.  The variables observed were: plant length, number of leaves, leaf color, number of branches, and leaf area.  The results of the study showed that there was no interaction between the level of shade and different doses of goat manure on the growth of Arachis pintoi on Mediterranean soil.  A shade level of 40%=N2 provides the best growth of Arachis pintoi. Goat manure at a dose of 20 tons ha-1=D2 tends to provide the best growth of Arachis pintoi.  It can be concluded that there is no interaction between the level of shade and different doses of goat manure on Mediterranean soil, a shade level of 40%=N2 and a dose of goat manure of 20 tons ha-1=D2 provide the best growth of Arachis pintoi.